Implementation of dialogic approach of teaching science in Ghanaian grade 7 science classroom - Boadi, Joseph (2019)
The aim of this study was to implement dialogic approach of teaching science in Ghanaian classrooms and how students response to this approach. Despite the moves to change curricula to be more student-centered, the approach of teaching science in Ghana remains authoritative and monologic. To achieve the aim of this research, this thesis carried out action research in grade 7 classrooms in Opoku Ware Junior High School, Ghana. During the action research, lessons were video recorded and students were randomly selected and interviewed. This study analysed the interview data using qualitative content analysis to answer the research questions. The responses from the students indicated that the dialogic approach of teaching science supported their understanding of the lessons and encouraged students’ active participation in the lessons. Major challenge confronted during the implementation of the dialogic approach of teaching science in the Ghanaian classroom was large class sizes. Though the introduction of the group activities helped the students to participate in the lesson, it would have been more effective if the class sizes were smaller.